Analisis Strategi Pengembangan Home Industry Woko Kretek (WK) Dalam Meningkatkan Pendapatan di Desa Woko Kecamatan Pajo Kabupaten Dompu - Haryanto, Dedi; Mulyati, Mulyati; Sumarni, Sumarni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the development strategy of Woko Kretek (WK) Home Industry in increasing income in Woko Village, Pajo District, Dompu Regency. This research was conducted in Woko Village, Pajo District, Dompu Regency with the research subjects being Home Industry owners and employees. The data analysis technique used is qualitative descriptive analysis. With the type of research using field research. The results of this study show 1). The development strategy carried out at Home Industry Woko Kretek (WK) is to increase income by selecting raw materials, creating quality products, setting affordable prices, developing human resources, increasing marketing. 2). Support and obstacles for Home Industry supporters are the support of facilities from the government, abundant and cheap raw materials. The inhibiting factors are the presence of illegal cigarette competition and limited capital